Validity of postexercise measurements to estimate peak VO2 in 200-m and 400-m maximal swims - Rodriguez, F. A.; Chaverri, D.; Iglesias, X.; Schuller, T.; Hoffmann, U. (International Journal of Sports Medicine, 2017)
To assess the validity of postexercise measurements to estimate oxygen uptake (VO2) during swimming, we compared VO2 measured directly during an all-out 200-m swim with measurements estimated during 200-m and 400-m maximal tests using several methods, including a recent heart rate (HR)/VO2 modelling procedure. 25 elite swimmers performed a 200-m maximal swim where VO2 was measured using a swimming snorkel connected to a gas analyzer. The criterion variable was VO2 in the last 20 s of effort, which was compared with the following VO2peak estimates: 1) first 20-s average; 2) linear backward extrapolation (BE) of the first 20 and 30 s, 3×20-s, 4×20-s, and 3×20-s or 4×20-s averages; 3) semilogarithmic BE at the same intervals; and 4) predicted VO2peak using mathematical modelling of 0-20 s and 5-20 s during recovery. In 2 series of experiments, both of the HR/VO2 modelled values most accurately predicted the VO2peak (mean =0.1-1.6%). The BE methods overestimated the criterion values by 4-14%, and the single 20-s measurement technique yielded an underestimation of 3.4%. Our results confirm that the HR/VO2 modelling technique, used over a maximal 200-m or 400-m swim, is a valid and accurate procedure for assessing cardiorespiratory and metabolic fitness in competitive swimmers.